NOWA REGULACJA USTAWOWA DZIAŁALNOŚCI GOSPODARCZEJ W POLSCE - Kuciński, Jerzy; Trzciński, Zenon (Wydział Prawa i Administracji UAM, 2000)
In tge beginning of their article the Authors present premises of voting and the range of regulation of the new law from November 19, 2000 - Law on Economic Activity and then they determine the notion itself of „economic activity” as understood in the new law together with principles of undertaking and performing it. Next they are occupied with a question how does this law shapes the role of an entrepreneur, his rights and duties, as well as with regulation of economic activity. The article is ended with an analysis of regulations comprised in the new law in relation to economic self-government and to the tasks of administration, both governmental and self-governmental.
NEW LEGAL REGULATION OF ECONOMIC ACTIVITY IN POLAND